1970
DOI: 10.1161/01.res.27.6.961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coronary Blood Flow and Perfusion Pressure on Left Ventricular Contractility in Dogs

Abstract: The effects of changes in coronary blood flow and coronary artery pressure on left ventricular (LV) contractility were determined in 18 animals. Dogs on cardiopulmonary bypass provided isovolumetric LV contractions during controlled perfusion of the coronary circulation. Coronary venous efflux, myocardial oxygen consumption, peak LV pressure, LV dp/dt, and the forcevelocity relations of the LV were determined at normal and at "supernormal" levels of flow and pressure. Coronary vasodilatation was obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

1972
1972
2003
2003

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 33 publications
1
30
0
1
Order By: Relevance
“…The Gregg phenomenon has been demonstrated in experimental models in which coronary flow is increased by pharmacological vasodilation, without an increase in perfusion pressure. 33 The most widely proposed mechanism for the phenomenon is that mechanical distension of myofibrils by adjacent distended intramyocardial vessels34,35 leads to increased contractility, perhaps by a localized Frank-Starling mechanism. An alternative explanation is that a surfeit of myocardial oxygen delivery leads to increased oxygen utilization,36 improved energetics with an increased phosphorylation potential, and augmented ATP utilization for contractile activity.…”
Section: Resultsmentioning
confidence: 99%
“…The Gregg phenomenon has been demonstrated in experimental models in which coronary flow is increased by pharmacological vasodilation, without an increase in perfusion pressure. 33 The most widely proposed mechanism for the phenomenon is that mechanical distension of myofibrils by adjacent distended intramyocardial vessels34,35 leads to increased contractility, perhaps by a localized Frank-Starling mechanism. An alternative explanation is that a surfeit of myocardial oxygen delivery leads to increased oxygen utilization,36 improved energetics with an increased phosphorylation potential, and augmented ATP utilization for contractile activity.…”
Section: Resultsmentioning
confidence: 99%
“…According to present knowledge, other factors that may alter the dP/dt values after increasing AP are shortening deactivation (21)(22)(23)(24), the Anrep effect (15,18,19) and variations in coronary flow (25) or coronary perfusion pressure (26). Previous studies from our laboratory have shown that large increases of developed force (27) and coronary perfusion (28) do affect left ventricular performance in the intact canine left ventricle.…”
Section: Discussionmentioning
confidence: 85%
“…It has been described that, in addition to myocardial ischemia, coronary perfusion pressure can affect cardiac mechanics interfering with intracellular calcium concentration (30,31) and sarcomere resting length (26,32). Abel and Reis (25) described an enhancement of cardiac performance following the increase of coronary Table 2 -Isometric contraction data of rats.…”
Section: Discussionmentioning
confidence: 99%
“…5, panel D). As may be seen from Table I Table II. Sodium nitrite was specifically selected for this study as it reportedly does not induce a positive inotropic effect hlen administered to isolated cat papillary muscle preparations (19,20). Papaverine likewise, if anything, has been shown to depress ventricular contraction in Langendorff perfused frog and turtle hearts (21,22) which, it may be presumed, are in a state of maximal or near maximal vasodilation.…”
Section: Resultsmentioning
confidence: 99%